Analytical determination of load resistance value for MQ-series gas sensors: MQ-6 as case study - Ajiboye A. T.; Opadiji J. F.; Yusuf A. O.; Popoola J. O. (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
The MQ-series gas sensors are attractive candidates in the area of gas concentration sensing due to their high sensitivity and low cost. Even though the sensor circuit sensitivity and sensor power dissipation level both depend on load resistance, the process of the load resistance selection has not been well researched, hence the need for this study. The derivation of model equations for determining the sensor circuit sensitivity and sensor power dissipation is presented. The derived equations were used to investigate a typical scenario of MQ-6 gas sensor under the influence of liquified petroleum gas (LPG). The variation of sensitivity with load resistance and that of power dissipation with sensor resistance were parametrically investigated. The load resistance that yields maximum sensor circuit sensitivity with the maximum sensor power dissipation less than the set threshold is the candidate resistance for the sensor circuit. The 20 kΩ load resistance recommended for MQ-6 in the datasheet was authenticated in this study, yielding the maximum possible sensor circuit sensitivity and tolerable sensor power dissipation of 0.195 mV/ppm and 3.125×10−4 W, respectively.